Study of pressure-balanced oil-filled (PBOF) technology. (15th September 2022) - Song, Wentao; Yang, Cuibo; Cui, Weicheng; Lei, Yi; Hong, Jin; Wang, Zhenhua; Hu, Zhiyang
Abstract: Underwater wet-mateable connectors (WMCs) can be mated and de-mated in the subsea environment, which have been widely used in the ocean engineering. Since the high ocean pressure will cause a tremendous mate and de-mate force, the pressure-balanced oil-filled (PBOF) technology is introduced which can make WMCs operated at the depth of even 11, 000 m. PBOF technology further gave birth to underwater pressure compensators (UPCs) which can reduce the mass of pressure housings used in autonomous underwater vehicles (AUVs) and can eliminate the influence of the ambient pressure on the hydraulic system of underwater robots. This paper aims to give a detailed investigation of PBOF technology and to develop a resilient bladder used in WMCs. First, the differential pressure equation of the bladder is derived. Second, an innovative finite element analysis (FEA) model involving fluid-solid interaction (FSI) is proposed to verify the theory by using ANSYS Mechanical and APDL co-simulation. Finally, a novel resilient bladder with a simple structure and low-cost is developed, and a prototype of UPC is manufactured to test the bladder's performance. This paper is the first report to publicly reveal the mechanism of PBOF technology in the aspects of theory, simulation and test, which provides the design methods for the application of PBOF technology. Highlights: Pressure-balanced oil-filled (PBOF) technology is investigated in the aspects of theory, simulation and test. The differential pressure equation is deduced and validated both by the proposed FEA model and the tests. A novel resilient bladder used in wet-mateable connectors was developed, which has a simple structure and low-cost. Using soft rubber can effectively reduce the differential pressure of bladders and can improve the bladder's sensitivity.